Development of hemoglobin typing control materials for laboratory investigation of thalassemia and hemoglobinopathies - Sakorn Pornprasert (2018)
© 2016 by De Gruyter 2016. Background: To date, the hemoglobin (Hb) typing control materials for laboratory investigation of thalassemia with low (1.8%-3.2%) and high (4%-6%) levels of HbA2 are available but there are no Hb typing quality control materials for analysis of thalassemia and hemoglobinopathies which are highly prevalent in South-East Asian countries. The main aim of the present study was to develop the lyophilized Hb typing control materials for laboratory investigation of thalassemia and hemoglobinopathies that are commonly found in South-East Asia. Methods: Erythrocytes of blood samples containing Hb Bart's, HbH, HbE, HbF, Hb Constant Spring (CS), Hb Hope, and Hb Q-Thailand were washed and dialysed with 0.85% saline solution. The erythrocytes were then lysed in 5% sucrose solution. The lyophilized Hb typing control materials were prepared by using a freeze drying (lyophilization) method. The high performance liquid chromatography (HPLC) analysis of lyophilized Hb was performed after the storage at -20 °C for 1 year and also after reconstitution and storage at 4 or -20 °C for 30 days. In addition, the Hb analysis was compared between the three different methods of HPLC, low pressure liquid chromatography (LPLC) and capillary electrophoresis (CE). Results: Following a year of storage at -20 °C, the HPLC chromatograms of lyophilized Hb typing control materials showed similar patterns to the equivalent fresh whole blood. The stability of reconstituted Hb typing control materials was also observed through 30 days after reconstitution and storage at -20 °C. Moreover, the Hb typing control materials could be analyzed by three methods, HPLC, LPLC and CE. Even a degraded peak of HbCS was found on CE electropherogram. Conclusions: The lyophilized Hb typing control materials could be developed and used as control materials for investigation of thalassemia and hemoglobinopathies.